The Correlation of Coral Reef Cover and Rugosity with Coral Reef Fish Density in East Java Waters - Wahyu Andy Nugraha; Faizun Mubarak; Eko Husaini; Hasyim Evendi (Faculty of Fisheries and Marine Universitas Airlangga, 2020)
HighlightsCoral cover, rugosity, and reef fish abundance was determinedThe relationship between coral cover and rugosity and fish abundance was analyzed.Coral cover in East Java were categorized as medium – good.The rugosity index and the fish abundance were highest in Bangsring Waters.There are no relationships between coral cover and fish abundance, but there is relationship between rugosity and fish abundance.AbstractA coral reef is one of the most complex and specific ecosystems in a tropical area. It is identified by its high productivity and biodiversity. This research aims to discover the percentage of coral reef cover and rugosity, as well as the fish abundance in several locations in East Java, Indonesia. In addition, this research aims to investigate the correlation of coral reef cover and rugosity with the density of coral reef fish. This research was conducted in three locations, i.e., Bangsring Waters of Wongsorejo District, Banyuwangi Regency; Gili Noko Bawean Island, Gresik Regency; and Kramat Island, Gili Genting District, Sumenep Regency. This research employed the Line Intercept Transect (LIT) method to calculate the percentage of coral reef cover, the Chain Intercept Transect (CIT) method to determine the coral reef rugosity, and the Belt Transect method to estimate the fish abundance. From this research, it was revealed that the highest coral reef cover was in Bawean waters, while the highest rugosity was in Bangring waters. In addition, the highest coral reef fish density was in Bangsring waters. Meanwhile, the coral reef fish density did not correlate with the percentage of coral reef cover. In contrast, it correlated with the coral reef rugosity.